Transition submergence and hysteresis effects in three-foot cutthroat flumes - Torres, Alfonso F., author; Merkley, Gary P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
New and detailed hydraulic laboratory measurements for a 3-foot Cutthroat flume with four different throat widths were collected and analyzed. It was found that there is no definitely observable transition submergence at which the regime changes from free to submerged, and vice versa. It was also found that no hysteresis effect on the calibration is observable in the 3-ft Cutthroat flume when moving from low to high submergence, or from high to low submergence. The laboratory data demonstrate that previously published transition submergence, St, values do not accurately describe the hydraulic behavior of this Cutthroat flume because St is not constant for given flume dimensions — it varies with flow rate. Various criteria were applied to the laboratory data to define the curvilinear relationship of St with flow rate, thereby providing a more accurate application of the traditional free- and submerged-flow equations, in those cases where their continued use is desired. The observed St at the maximum discharge in each of the four throat widths was strongly correlated with the previously published St values.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.